(untitled) (Experimental biology, 2026)
The physiological condition of young-of-the-year mirror carp (Cyprinus carpio) reared under pond aquaculture conditions and infected with myxosporeans was investigated. The study aimed to assess the effects of myxosporean infection on the physiological and hematological parameters of cyprinid fishe. Infected individuals exhibited pronounced clinical signs of the disease, frequently accompanied by mortality. Hematological analysis revealed high levels of monocytes, neutrophils (32.68%), and white blood cells (257.6× 10⁹/L) compared to the norm. Elevated differential leukocyte counts indicate an increased defense reaction of the organism under conditions of parasitic invasion. Histological examination of gills, heart, intestine, hepatopancreas and musculature revealed the presence of intracellular, interstitial, and diffuse localization of parasitic mucous spores (Myxozoa: Myxosporea: Myxobolidea). Necrosis, desquamation, hyperplasia and a dramatic increase of mast cells in the gills of the studied fish are due to both small intracellular plasmodia and spores located inside tissue cysts. The increase in the number of mast cells in the gills of fish in localization of mucous parasites is associated with the need to maintain homeostasis of the immune system. The pathological effect of myxosporean plasmodia on organs of the digestive tract were established, causing necrosis, disruption of cell absorption and transport processes, as well as reduction of the height of prismatic epithelial cells with degeneration of microvilli on their apical surface. Intracellular parasitism of uninucleate and binucleate mucous myxosporeans were also observed in the cells of the hepatopancreas and heart. Necrotic foci located on the skin of the fish were a manifestation of the inflammatory process and hemorrhages in the muscles due to parasitic invasion.